Laser induced graphene based flexible gas sensor for wearable electronics - Büyükturgay, Mehmet Mert (Lisansüstü Eğitim Enstitüsü, 2020)
From the past to the present, the most important thing to consider when developing defense systems is the production of original technology. The industrial power of a country is dependent on its technology. In this sense, it is important for countries to improve their original technologies. Technology is also important in the means of the privacy, reliability, and foreign dependency of defense systems. Production and development of high technology defense systems open a country's way to the domination of the world market, hence increasing the living standards of its citizens. This situation causes competitiveness in the field and in order to establish military domination, it is essential for countries to be able to produce and improve high-technology defense systems. Electronic technologies are also important in the defense systems industry. Since electronic technologies are widely used, engineers usually spend more shift hours designing and developing these products. There are lots of parameters in order to make these products ideal to be used in the defense systems industry. It is important and necessary for defense systems to be smaller in size, lightweight, with less effort and power required, practical, and faster in data transmitting. However, it may not always be easy to meet these necessities. In designing a product, just meeting one of these necessities may require a million dollars. The widespread use of electronic technologies results in the formation of new systems that are smaller, lightweight, and microchip controlled. In a changing and developing world, software updates of defense systems are also very important to function effectively. At the same time, the textile industry has recently begun to shift from traditional textile products to intelligent new textiles that process information to meet the demands and requirements of the defense industry. This situation resulted in engineering fields such as material science, electronics, and chemistry leading the textile industry and in the formation of a new multidisciplinary working area. Sensors compose almost the entire range of the smart textile field and unlike traditional textiles, it is a field open to new technological developments. Smart textiles are usually designed and developed for military technologies and the health sector. Wearable technologies complete duties such as obtaining and processing important data from the environment and simultaneously sending and visualizing these data to different sources. Smart clothing developed for area scanning and search and rescue teams may provide life safety for both search and rescue and military staff. They may also make any intervention more effective. Furthermore, information such as hazardous toxic gasses, amount of oxygen, and temperature of the potential risk zone and accident area may be obtained through this technology. This information is sent to different sources simultaneously and necessary measures are taken immediately. With the development of this system, risk analysis may be carried out in more detail, based on the information obtained from risky regions. The smart sensors may also be used in the exploration of the risky area; hence making the planning and application of the required intervention safer. Gas sensors play a major role in war fields and accident areas. Nowadays many countries are producing various chemical and biological weapons, so it is a necessity for every country to develop its own defense systems and take necessary precautions. New smart gas sensors are being developed as protection systems in case of the usage of these weapons. Gas sensors are not only used in the field of military defense systems; they are also used in companies where chemicals are frequently used and in highly populated regions in order to protect the health of workers and individuals by distinguishing hazardous and non-hazardous gasses in the air. Today, although many types and functions of commercial products are produced, problems in detecting hazardous gasses have not been solved completely. The problems that usually vary according to the type of sensor and need to be solved are as follows; the size of the sensor may not be small enough, low sensitivity and selectivity, long response time, not being suitable for long-term use, easy abrasion, sensitivity to movement, measurement errors due to environmental factors, high energy consumption, and difficulties in production and high costs. Briefly, more advanced and smart devices are needed, in order to detect what type of gasses are in the air. In this study, different sensor technologies and systems were studied to detect toxic or hazardous gasses. A major part of this study consists of research that accounts for precision, selectivity, response intervals, flexibility, resistance, size, and portability of the sensors. Even in their applications in daily life, sensors should be able to obtain data while they are in motion and transmit this data to distant sources. Therefore, in order to prevent the limitation of motion, the sensors should be portable and flexible enough to wrap the body easily. Wearable sensors that are designed compatible with clothing are more effective and useful than handheld sensors. The aim of this study is to determine whether the environment is dangerous or not in terms of gas type and to ensure that this information is transmitted to the source. Since this study is designed in the means of wearable technology, the disadvantage of carrying any device is eliminated. In addition, with the help of the sensor and resistance meter on the clothing, instant toxic gas contact can be detected. Therefore, staff on duty are able to obtain data from the environment simultaneously and can act more precautious to the current situation. First, a 3D graphene sensor was produced on the polyimide PI film using laser direct writing to create direct ammonia gas sensors. At this stage, first, the CO2 laser to be used has been optimized, the focus of the laser has been determined and the optimum parameters that will affect the final product have been determined. Then, carbonization and graphitization processes were applied according to these parameters. However, the necessary software was previously installed on the CO2 laser to implement this phase. With the help of the "Inkspace" application, sensors are designed and drawn. Then, with the help of the "K40 Whisperer" driver, the previously drawn sensors were transferred to the memory of the laser. The laser system was controlled with this driver, the predetermined parameters were entered into the system and the laser engraving process was started. As a result of this process, the desired laser-induced graphene products were obtained. The bending test was applied to the graphene sensors obtained. The products that were successful in this test were tested again for resistance with the help of a digital multimeter. The samples obtained after these tests were used in the specially designed NH3 gas sensor system. After the LIG sensor specimens were obtained, the chamber was ready to be installed. NH3 gas sensor mainly consists of a bottle of ammonia gas (25%), a micro syringe, control switches, a jar for the gas mixing system, a jar for the chamber, 1 air fan, 2 pneumatic pipes (1 for gas inlet and 1 for gas outlet), a digital multi-meter and pre-produced graphene sensors. This test was done at room temperature and room atmosphere. First, a micro syringe was filled with a certain volume of NH3(25%); then it was injected into a gas mixing system. A certain concentration of ammonia gas(100ppm-1000ppm) was obtained by mixing with ambient air in the mixing system. After that, the first switch was turned on and the mixing gas vapor was transferred to the test chamber near the LIG sensor. The LIG specimen was placed inside the chamber. In this system, one of the control switches was used to transfer a certain concentration of ammonia gas to the chamber and the other switch was used to release the gas from the chamber. Thus, a certain concentration of ammonia gas was circulated in the chamber homogenously with the help of the air fan. The digital multimeter that was used in this chamber is able to show the resistance of the sensor when it was exposed to ammonia gas and the atmosphere. As a result of the changing ambient atmosphere, the resistance meter connected to the graphene sensor showed a resistance change due to NH3 gas contact. Therefore, ammonia gas sensing was carried out. As a result, a flexible graphene-based gas sensor was produced, which detects whether there is any ammonia gas as a warfare gas simulant in the atmosphere. The produced graphene-based gas sensors can operate at room temperature with high selectivity and low power consumption. Thus, this study can be an important candidate for today and future applications of wearable detectors in both military and many other fields.

Geçmişten günümüze, savunma sistemleri geliştirilirken dikkat edilmesi gereken en önemli husus özgün teknoloji üretimidir. Ülkelerin sanayi gücü, sahip oldukları teknolojilere bağımlıdır. Bu yolda izlenilmesi gereken politika ise mevcut özgün teknolojilerin geliştirilmesidir. Teknoloji, aynı zamanda savunma sistemlerinin gizliliği, güvenilirliği ve dışa bağımlılığı açısından çok önemlidir. İleri teknoloji ürünler üretip, geliştirmek; o ülkenin dünya pazarında egemenlik kurmasını ve refah seviyesini yükseltmesini sağlar. Bunun sonucunda, dünya üzerinde ciddi bir rekabet ortamı oluşur. Askeri üstünlük sağlanabilmesi için, yüksek teknoloji içeren savunma sanayii ürünlerini geliştirme ve üretme yeteneği ön plana çıkmaktadır. Elektronik teknolojiler, savunma sanayiinde çok büyük önem taşımaktadır. Elektronik ürünlerin kullanımının çok yaygın olması, bu ürünlerin tasarım geliştirmesinde mühendislerin uzun mesailer harcanmasına yol açmaktadır. Bu ürünlerin en ideal hale getirilmesi için gerekli pek çok parametre bulunmaktadır. Savunma sistemlerinin daha küçük, daha hafif, daha sağlam, daha az güç gerektiren, daha hızlı veri ileten, daha kullanışlı hale getirilmesi oldukça önemli ve gereklidir. Ancak, bu işlem çok da kolay değildir. Hali hazırdaki bir üründe, bu özelliklerden sadece bir tanesinin bile geliştirilmesi, milyonlarca doların o şirketin kasasına girebilmesine yetmektedir. Elektronik teknoloji her geçen gün yoğun olarak kullanıldıkça, yeni sistemlerin oluşmasını ve bu yeni sistemlerin giderek küçük, hafif tasarımlı mikroçip kontrollü hale gelmesini sağlamaktadır. Her gün değişen ve gelişen dünyada savunma sistemlerinin etkinliklerini sürdürülebilmesi için yazılımda yapılan güncellemeler de çok önemlidir. Aynı zamanda, tekstil sanayii de son zamanlarda savunma sanayisinin isteklerini ve gereksinimlerini karşılayabilmek için, geleneksel tekstil ürünlerinden, bilgiyi işleyen ve akıllı yeni tekstillere doğru yönelmeye başlamıştır. Bu durum; malzeme bilimi, elektronik ve kimya gibi mühendislik bölümlerinin tekstil sektörüne yön vermesine sebep olmuştur. Böylece, yeni bir multidisipliner çalışma ortamı oluşmuştur. Sensörler, akıllı tekstiller alanının neredeyse tamamını oluşturmaktadır ve geleneksel tekstillerden farklı olarak yeni teknolojik gelişmelere açık bir alandır. Akıllı yeni tekstiller genel olarak askeri teknolojiler ve sağlık sektörü için geliştirilmektedir. Giyilebilir teknolojiler, eş zamanlı olarak bulundukları ortamın önemli verilerini alıp, işleyip, farklı kaynaklara iletme ve görüntüleme gibi işleri yerine getirirler. Bölge tarama ve arama kurtarma görevleri için geliştirilen akıllı giysiler, askeri personelin ya da arama kurtarma ekibinin can güvenliğini sağlayabilir ve herhangi bir müdahalenin daha etkin olmasını sağlar. Böylece, risk içerebilecek bölgede veya kaza bölgesinde bulunan tehlikeli zehirli gazlar, ortamın oksijen miktarı ve sıcaklık bilgileri elde edilir. Bu bilgiler eş zamanlı olarak farklı kaynaklara ulaştırılır ve duruma uygun önlem alınmasını sağlar. Aynı zamanda, geliştirilen bu sistem ile riskli bölgelere ait bilgilere dayalı olarak tehlike analizi daha detaylı bir şekilde yapılabilmektedir. Tasarlanan akıllı sensörler, tehlikeli bölgenin keşif sürecini,müdahalenin planlanmasını ve gerçekleştirilmesini daha verimli ve güvenilir hale getirmek için kullanılabilir. Savaş alanlarında veya kaza bölgelerinde gaz sensörlerinin rolü çok büyüktür. Günümüzde pek çok ülke çeşitli kimyasal ve biyolojik silahlar üretmektedir. Haliyle, bu durumlara karşı ülkelerin savunma sistemlerini geliştirip, kendi gardlarını almaları gerekmektedir. Yeni tip akıllı gaz sensörleri tam da kimyasal ve biyolojik silah kullanımına karşı uyarı amacıyla üretilmiş ve hala günümüzde geliştirilmeye devam etmektedir. Gaz sensörleri sadece askeri savunma alanlarında kullanılmamaktadır. Aynı zamanda, kimyasalların sıkça kullanıldığı şirketlerde ve kirliliğin fazla olduğu çeşitli bölgelerde çalışan veya yaşayan canlıların sağlığı için havada zehirli gaz olup olmadığını ayırt etmekte de kullanılmaktadır. Günümüzde, pek çok türde ve işlevde ticari ürün üretilmesine rağmen tehlikeli gazların tespit edilmesindeki problemler tamamen çözülebilmiş değildir. Genellikle sensör türüne göre değişen ve sık görülüp çözülmesi gereken sorunlar şu şekildedir: Sensörün ebatlarının yeterince küçük olmaması, hassasiyetin yetersizliği, düşük seçicilik, uzun cevap süresi, uzun süreli kullanımlara uygun olmaması, kolay aşınabilmesi, harekete karşı duyarlı olması, çevresel faktörlerden oluşan ölçüm hataları, yüksek enerji tüketimi, üretimde zorluklar ve yüksek maliyetler. Kısacası, havada bulunan gazların neler olduğunu tespit edebilmek için daha gelişmiş ve daha akıllı cihazlara ihtiyaç vardır. Bu sebepten dolayı, bu çalışmada zehirli veya tehlike yaratabilecek gazların tespit edilebilmesi için daha farklı sensör teknolojileri ve sistemler üzerine çalışılmıştır. Bu çalışmanın önemli bir kısmı sensörlerin hassasiyet, seçicilik, cevap süresi, esneklik, dayanıklılık, boyut ve taşınabilirliğini geliştirmeye yönelik araştırmalardan oluşur. Sensörlerin günlük hayattaki uygulamalarında bile hareket halindeyken verileri alıp uzak kaynaklara iletebilmesi gerekir. Bu nedenle, hareketi sınırlamaması amacıyla bu sensörlerin kolay taşınabilir olması, hatta vücudu kolayca sarabilecek şekilde esnek olması gerekir. Elde taşınabilen sensörlerden ziyade kıyafetle bir uyum içerisinde tasarlanmış giyilebilir sensörler çok daha verimli ve kullanışlıdır. Bu çalışmanın amacı, içinde bulunulan ortamın, gaz türü açısından tehlikeli olup olmadığını tespit edip bu bilginin kaynağa iletilmesini sağlamaktır. Bu çalışma giyilebilir teknoloji olarak tasarlanması sebebiyle herhangi bir cihaz taşıma dezavantajı da ortadan kalkmış olur. Ayrıca, giysideki sensör ve direnç ölçer sayesinde anlık zehirli gaz teması tespit edilebilmektedir. Böylece, görev başındaki personel bulunduğu ortamdan anında eş zamanlı olarak haberdar olabilmektedir ve duruma uygun daha temkinli hareket edebilmektedir. Bu çalışmada ilk olarak, doğrudan amonyak gazı sensörleri oluşturmak için lazer doğrudan yazma kullanılarak poliimid PI filmi üzerinde bir 3D grafen sensörü üretilmiştir. Bu aşamada ilk olarak, kullanılacak olan CO2 lazeri optimize edildi, lazerin odak noktası belirlendi ve son ürünü etkileyecek optimum parametreler belirlendi. Daha sonra, belirlenen bu parametrelere göre karbonizasyon ve grafitizasyon işlemleri uygulandı. Ancak, bu aşamanın uygulanması için daha önceden CO2 lazerine gerekli yazılımlar yüklendi. ―Inkspace‖ uygulaması yardımıyla sensörler tasarlandı ve çizildi. Ardından, ―K40 Whisperer‖ sürücüsü yardımıyla, önceden çizilen sensörler lazerin hafızasına aktarıldı. Bu sürücü ile lazer sistemi kontrol edildi, önceden belirlenen parametreler sisteme girildi ve lazer oyma prosesine başlandı. Bu proses sonucunda, arzu edilen lazer indüklenmiş grafen ürünleri elde edildi. Elde edilen grafen sensörlerine önce bükülme testi uygulandı. Bu testte başarılı olan ürünlere de multimetre yardımıyla direnç testi yapıldı. Bu testlerin ardından, elde edilen numuneler özel tasarlanan NH3 gaz sensörü sisteminde kullanıldı. Bu sistemde bir adet direnç ölçer, bir şişe sıvı amonyak, iki adet kapaklı cam şişe, 2 adet pnömatik hortum (1 tanesi gaz girişi ve 1 tanesi de gaz çıkışı için) ve önceden üretmiş olduğumuz grafen sensörler kullanıldı. Bu test oda sıcaklığında ve oda atmosferinde yapıldı. İlk olarak, test ortamına belirli bir konsantrasyonda NH3 gazı gönderildi. Değişen ortam atmosferi sonucunda, grafen sensörüne bağlanan direnç ölçer, NH3 gazı ile bir direnç değişimi gösterdi. Sonuç olarak, ortamda savaş gazı benzeri olan amonyak gazı olup olmadığını tespit eden grafen bazlı esnek bir gaz sensörü üretilmiş oldu. Üretilmiş olan grafen bazlı gaz sensörleri, yüksek seçicilik ve düşük güç tüketimi ile oda sıcaklığında çalışabilmektedir. Böylece, bu çalışma hem askeri hem de diğer alanlarda, giyilebilir detektörlerin günümüzdeki ve gelecekteki uygulamaları için önemli bir aday olabilir.
Giyilebilir elektronikler için lazer kaynaklı grafen bazlı esnek gaz sensörü
Thesis (M.Sc.) -- İstanbul Technical University, Graduate School, 2022
Keywords: smart textile; akıllı tekstil; gas sersor; gaz sensörü; wearable technology; giyilebilir teknoloji